2019
DOI: 10.1101/gr.249805.119
|View full text |Cite
|
Sign up to set email alerts
|

The subgenomes show asymmetric expression of alleles in hybrid lineages of Megalobrama amblycephala × Culter alburnus

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 46 publications
3
39
2
Order By: Relevance
“…In the present study, we also cloned culter mrap2a and mrap2b , and showed that similar to MRAP2s of other species, culter MRAP2a and MRAP2b had one potential N -linked glycosylation site in the N-terminal domain and a single highly conserved TMD ( Figure 2 and Supplementary Figure 3 ). Based on culter genomic data ( 43 ), we did not identify MRAP1 in topmouth culter, consistent with the hypothesis that MRAP1 is lost in lobe-finned fish, amphibians, and reptiles ( 39 , 56 ). The tissue expression data showed that mrap2a and mrap2b were highly expressed in the central nervous system ( Figures 3C–F ), similar to the expression of mc4r , indicates that caMRAP2a or caMRAP2b might modulate MC4R signaling in the central nervous system.…”
Section: Discussionsupporting
confidence: 79%
“…In the present study, we also cloned culter mrap2a and mrap2b , and showed that similar to MRAP2s of other species, culter MRAP2a and MRAP2b had one potential N -linked glycosylation site in the N-terminal domain and a single highly conserved TMD ( Figure 2 and Supplementary Figure 3 ). Based on culter genomic data ( 43 ), we did not identify MRAP1 in topmouth culter, consistent with the hypothesis that MRAP1 is lost in lobe-finned fish, amphibians, and reptiles ( 39 , 56 ). The tissue expression data showed that mrap2a and mrap2b were highly expressed in the central nervous system ( Figures 3C–F ), similar to the expression of mc4r , indicates that caMRAP2a or caMRAP2b might modulate MC4R signaling in the central nervous system.…”
Section: Discussionsupporting
confidence: 79%
“…This may be explained if trans divergence results from a limited activity of a TF in one of the species, which indeed appears to explain a considerable fraction of trans-effects we observe. This may provide a mechanistic explanation for the phenomenon of genome asymmetry that was reported before in a variety of organisms (Feldman et al, 2012;Lemos et al, 2008;Ren et al, 2019) whereby the phenotypic manifestation of some traits, including gene expression patterns, favors one genome over the other rather than being intermediate.…”
Section: Discussionmentioning
confidence: 57%
“…All available Sox genes were identified in the zebrafish genome 1 . These Sox genes were used to search for their respective BSB and 2nRCC counterparts in the available BSB and 2nRCC genomic resources (project ID: PRJNA481500) using Blast (V2.5.0) software (Chen et al, 2019;Ren et al, 2019). The CDs lengths and aa numbers of the putative Sox genes were identified from the BSB and 2nRCC genomes.…”
Section: Preparation Of Chromosome Spreadsmentioning
confidence: 99%
“…The goldfish (2nRCC, 2n = 100) is raised over all Asia for food and as an ornamental pet (Liu et al, 2016;Chen et al, 2019), while Megalobrama amblycephala (blunt snout bream, 2n = 48, BSB) is an economically important freshwater fish (Ren et al, 2019). In previous studies, we artificially obtained fertile allotetraploids (4nRB, 4n = 148, F 1 ) from the distant hybridization of 2nRCC (♀) × BSB (♂) (Liu et al, 2007).…”
Section: Introductionmentioning
confidence: 99%